BAIAP2L2 Inactivation Does Not Affect Stereocilia Development or Maintenance in Vestibular Hair Cells - Yan, Keji; Qu, Chengli; Wang, Yanfei; Zong, Wen; Xu, Zhigang (Frontiers in Molecular Neuroscience, 2022)
Hair cells are mechanosensitive cells in the inner ear, characterized by dozens to hundreds of actin-based stereocilia and one tubulin-based kinocilium on the apical surface of each cell. Two types of hair cells, namely cochlear hair cells and vestibular hair cells (VHCs), are responsible for the sensation of sound and balancing information, respectively. In each hair cell, the stereocilia are organized into rows of increasing heights with the mechano-electrical transduction (MET) channels localized at the tips of shorter-row stereocilia. A so-called “row 2 protein complex” also localizes at the tips of shorter-row mechanotransducing stereocilia, which plays important roles in the maintenance of mechanotransducing stereocilia. Recently, we and others identified BAIAP2L2 as a new component of row 2 complex. Baiap2l2 inactivation causes degeneration of the mechanotransducing stereocilia in cochlear hair cells, and leads to profound hearing loss in mice. In the present work, we examined the role of BAIAP2L2 in the VHC stereocilia. Confocal microscopy reveals that BAIAP2L2 immunoreactivity is localized at the tips of shorter-row stereocilia in VHCs. However, stereocilia development and maintenance are unaffected in Baiap2l2–/– VHCs. Meanwhile, MET function of VHCs as well as vestibular functions are also unaffected in Baiap2l2–/– mice. Further investigations show that the stereociliary tip localization of CAPZB2, another known row 2 complex component, is not affected in Baiap2l2–/– VHCs, consistent with the unaltered stereocilia morphology. Taken together, our present data show that BAIAP2L2 inactivation does not affect vestibular hair cell stereocilia.